1996
DOI: 10.1007/s002640050077
|View full text |Cite
|
Sign up to set email alerts
|

Tension-band laminoplasty of the cervical spine

Abstract: A new laminoplasty of the cervical spine has been developed using preserved ligaments as a tension-band. The laminae were enlarged in an open-door fashion and spacers inserted to maintain the spinolaminoligamentous complex intact. The stretched ligaments exerted a tension-band effect on the spacers and stabilised them so that neck movements could be started as soon as bleeding stopped. The spacers were iliac grafts, or were made of a bioactive ceramic which proved more satisfactory. The results of 102 cases wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(33 citation statements)
references
References 7 publications
0
33
0
Order By: Relevance
“…Historically, many authors describe a laminoplasty performed with resection of the spinous processes to prevent "crowding" in extension, to provide room for bone graft spacers, and to prevent a loss in cervical ROM. 12,19,20,24 Conversely, others describe the importance of maintaining this dorsal tension band, 28 and a recent clinical trial showed that retention of these dorsal elements may prevent loss of sagittal alignment at 1-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Historically, many authors describe a laminoplasty performed with resection of the spinous processes to prevent "crowding" in extension, to provide room for bone graft spacers, and to prevent a loss in cervical ROM. 12,19,20,24 Conversely, others describe the importance of maintaining this dorsal tension band, 28 and a recent clinical trial showed that retention of these dorsal elements may prevent loss of sagittal alignment at 1-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…7,8,13,22,25,27 Others suggest that the muscular attachments to C-7 do not influence long-term outcomes, 5 and that facet joint disruption may be more important in the development of postlaminoplasty neck pain and deformity. 20 There are few reports that address the preservation 26,28 or partial preservation 29 of the ISLs. Unfortunately, however, unless clearly stated, it is often difficult to determine if the terminal ligaments are spared in a given study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various materials are used to maintain the enlarged spinal canal such as thread 3) , autogeneous bone (spinous process 4,5) , iliac bone 2,6) ), hydroxyapatite spacer [7][8][9][10][11][12][13][14][15][16][17] , and titanium plate and screw 18,19) . Double-door type was first developed by Kurokawa in the late 1970s and reported in 1982 2) .…”
Section: Introductionmentioning
confidence: 99%